PENGARUH PENDEKATAN KETERAMPILAN PROSES SAINS TERHADAP PEMAHAMAN KONSEP FISIKA - Riskawati; Ali, Muhammad; Kamaluddin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to determine whether there was an effect of the science process skills approach to understanding the concept of physics in class VIII students of SMP Negeri 1 Sirenja. The type of research used was a quasi-experimental design with the equivalent, pretest-posttest design. The sample was selected using purposive sampling technique. Class VIIIA as the experimental class was treated using the science process skills approach and class VIIIB as the control class which was treated using the expository approach. The instrument used was a test of understanding the concept of physics in the form of multiple choice which had been tested. Based on the results of data processing, for the experimental class the mean final test score was 16.04 with a classical completeness value of 66.83% with a standard deviation of 4.18. For the control class, the mean final test score was 12.09 with a classical completeness value of 50.38% with a standard deviation of 4.66. From the results of data analysis, t-count> t-table, this indicated that the Hypothesis H1 is accepted. Thus it can be concluded that there is an effect of the science process skills approach to understanding the concept of physics in class VIII students of SMP Negeri 1 Sirenja.